Comparison of indirect arterial blood pressure values measured in five anatomical sites in awake dogs - Jiménez-Ballén, Valentina (2018)
This study aimed to determine possible significant variations in awake dogs in blood pressure between the four limbs, including the tail. The diastolic, systolic, and mean arterial pressures were taken using the SunTech Medical® equipment, using the oscillometry technique, in each of the limbs and the tail of 17 canine patients in a pet clinic in Bogotá, Colombia. No significant differences were found between the diastolic, systolic, and mean blood pressure values between each of the limbs and the tail.